Experiences of South African multiparous labouring women using the birthing ball to encourage vaginal births - Sindiwe James; Melissa Hudek (AOSIS, 2017)
The article explores the experiences of South African multiparous labouring women on their use of the birthing ball during the first stage of labour. The authors used a qualitative research approach using unstructured audiotaped interviews as the data collection method and data were collected over a period of one calendar month. The sample for the study were women who were six hours to six weeks post-delivery, had at least one child already, used the birthing ball, were on no medication, and had delivered a live infant. The sample consisted of twelve purposively selected participants, two of whom were used for the pilot study. The data analysis method was Data Analysis Spiral. The authors made use of an independent coder to assist with coding the data and three major themes were identified. The results revealed that the labouring women experienced the birthing ball as a useful labour tool, as shortening the labour process and as empowering them during labour.